Penerbitan Sertipikat Pengganti Hak Atas Tanah Karena Hilang: (Studi Di Kantor ATR/BPN Kabupaten Sumbawa) - Sidra Anantara; Muhammad Irfan (Private Law, 2023)
This research aims are to know legal force and to know form of legal protection on the land rights holder of substitute certificate because of the old certificate is putted as debt guarantee by other party. Type of this research was empiric legal research, which applied statute, conceptual and case approaches. Legal force of substitute certificate if the old certificate is found, based on the research’s result it can be explained that if one certificate is declared missing by the owner, and had been requested a new certificate, in Article 58 Government Regulation Number 24 of 1997 on Land Registration on the replacement of certificate because of damages or certificate form renewal, the old certificate will be detained or destroyed. Legal protection for the substitute certificate holder in principle is the same with the certificate holder in general which it can be the proof of a right, which applies as strong evidence. This matter can be seen in Article 32 paragraph (1) Government Regulation Number 24 of 1997.